Pregabalin in childhood epilepsy: a clinical trial study - MOLLAMOHAMMADI*, Mohsen; TONEKABONI, Seyed Hassan; PIRZADEH, Zahra; VAHEDIAN, Mostafa (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Mollamohammadi M, Tonekaboni SH, Pirzadeh Z, Vahedian M . Pregabalin in Childhood Epilepsy: A Clinical TrialIran J Child Neurol. 2014 Autumn;8(4): 62-65. Abstract Objective The prevalence of active epilepsy is about 0.5–1%, and approximately 70% of patients are cured with first anti-epileptic drugs and the remaining patients need multiple drugs. Pregabalin as an add-on therapy has a postive effect on refractory seizures in adults. To the best of our knowledge, there is no research with this drug in childhood epilepsy. We use pregabalin in children with refractory seizures as an add-on therapy. The objective of this study is to evaluate the effects of pregabalin in the reduction of seizures for refractory epilepsy. Material & Methods Forty patients with refractory seizures who were referred to Mofid Children’s Hospital and Hazrat Masoumeh Hospital were selected. A questionnaire based on patient record forms, demographic data (age, gender,…), type of seizure, clinical signs, EEG record, imaging report, drugs that had been used, drugs currently being used, and the number of seizures before and after Pregabalin treatment was completed. We checked the number of seizures after one and four months. Results After one month, 26.8% of patients had more than a 50% reduction in seizures and 14.6% of these patients were seizure-free; 12.2% had a 25–50% reduction; and approximately 61% had less than a 25% reduction or no change in seizures. After the fourth month, 34.1% of patients had more than a 50% reduction in seizures and 24.4% of these patients were seizure-free. Additionally, 65.9% of patients had less than 50% reduction in seizures (9.8% between 25–50% and 56.1% less than 25% or without improvement). Conclusion We recommend Pregabalin as an add-on therapy for refractory seizures (except for myoclonic seizures) for children. References Kwan P., Brodie MJ. Early identification of refractory epilepsy. N Engl J Med 2000;342(5):314-9. Mikati MA. Seizures in childhood. In: Kliegmann RM, Behrman RE, Jenson HB, Stanton BF, editors. Nelson Textbook of Pediatrics. 19th ed. Philadelphia, Pa:Saunders Elsevier. 2011.P.2013-2039. Camfield PR, Camfield CS. Pediatric Epilepsy. In: Swaiman KF, editors. Swaiman`s pediatric neurology: Principles and Practice.7th ed. Edinburgh: Elsevier Saunders; 2012.P 703-710. Piña-Garza EJ. Fenichel’s clinical pediatric neurology. Altered States of Consciousness. 7th ed. Elsevier Saunder. 2013.P.47-75. Austin JK, Smith S, Risinger MW, McNehs AM. Childhood epilepsy and asthma comparison of quality of life. Epilepsia 1994:35(3):608-15. Farvwell JR, Dodrill CB, Batzel LW. Neuropsychological abilities of children with epilepsy. Epilepsia 1985;26(5):395-400. Kotagal P, Rothner AD, Erenberg G, Cruse RP, Wyllie E. Complex partial seizures of childhood onset. Arch Neurol 1987:44(11):1177-80. Miller R, Frame B, Corrigan B, Burger P, Backbrader H, Garofalo EA, et al. Exposure- response analysis of pregabalin add- on treatment of patients with refractory partial seizures. Clin Pharmacol Ther 2003;73(6):491-505. Fink K, Dooley DJ, Meder WP, Suman-Chauhan N, Duffy S, Clusmann H, et al. Inhibition of neuronal ca(2+) influx by gabapentin and pregabalin in the human neocortex. Neuropharmacology 2002;42(2):229-36. Topol A. Pregabalin for epilepsy. New medicines profile 2004 November; (04/12):1-3. Arroyo S, Anhut H, Kugler AR, Lee CM, Knapp LE, Garofalo EA, et al. Pregabalin add-on treatment: a randomized, double-blind, placebo-controlled, doseresponse study in adults with partial seizures. Epilepsia 2004; 45(1):2-7. Beydoun A, Uthman BM, Kugler AR, Greiner MJ, Knapp LE, Garoflo EA. Safely and efficacy of two pregabalin regimens for add-on treatment of partial epilepsy. Neurology 2005;64(3):475-80. French JA, Kugler AR, Robbins JL, Knapp LE, Garoflo EA. Dose-response trial of pregabalin adjunctive therapy in patients with partial seizures. Neurology 2003;60(10):1631-7. Carreno M, Maestro I, Molins A, Donaire A, Falip M, Becerra JL, et al. Pregabalin as add-on therapy for refractory seizures in every day clinical practice. Seizure 2007;16(8):709-12. Jan MM, Zuberi SA, Alsaihati BA. Pregabalin: Preliminary experience in intractable childhood epilepsy. Pediatr Neurol 2008;40(5):347-50. Chisanga E, Manford M. Pregabalin drug information. NHS foundation trust. March 2013. Gil-Nagel A. Zaccara G. Baldinetti F. Leon T. Add-on treatment with pregabalin for partial seizures with or without generalization: pooled data analysis of four randomized placebo-controlled trials. Seizure 2009;18(3):184-92.